Peran keluarga dalam menunjang personal hygiene pada lansia di Desa Lam Lumpu Kecamatan Peukan Bada Kabupaten Aceh Besar - Surawati Surawati; Erlia Rosita (Journal of Health and Therapy, 2025)
The role of the family is very important in ensuring the elderly's personal hygiene, because the decline in their physical abilities affects their independence in maintaining personal hygiene and health. The study aims to analyze the relationship between family role and personal hygiene among the elderly in Lam Lumpu Village, Peukan Bada District, Aceh Besar Regency. This research method is a correlational analysis with a cross-sectional study design, using a purposive sampling technique with a sample of 55 respondents. Data collection used a questionnaire consisting of demographic data, a questionnaire on the role of the family in personal hygiene, and a personal hygiene observation sheet. The study found that the family's role was in the good category, and the elderly's personal hygiene was in the fulfilled category. This study found a significant relationship between family role and personal hygiene among the elderly in Lam Lumpu Village, Peukan Bada District, Aceh Besar Regency. The Village Government is advised to initiate education and training programs for elderly care families, in collaboration with the community health center, to provide elderly-friendly bathroom facilities and equipment to support the elderly's personal hygiene.